2021
DOI: 10.31635/ccschem.020.202000374
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Anti-Markovnikov Hydrocarboxylation of Acrylates and Styrenes with CO 2

Abstract: Light-driven carbon dioxide (CO 2 ) capture and utilization is one of the most fundamental reactions in Nature. Herein, we report the first visible-light-driven photocatalyst-free hydrocarboxylation of alkenes with CO 2 . Diverse acrylates and styrenes, including challenging tri-and tetrasubstituted ones, undergo anti-Markovnikov hydrocarboxylation with high selectivities to generate valuable succinic acid derivatives and 3-arylpropionic acids. In addition to the use of stoichiometric aryl thiols, the thiol ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 46 publications
0
60
1
Order By: Relevance
“…[ 1 , 2 , 3 ] Recently Lan and Yu introduced a photochemical approach to a range of α,β‐unsaturated esters providing good yields of the corresponding β‐hydrocarboxylated products, using stoichiometric or catalytic aromatic thiols. [3a] Romo, utilizing the conditions originally reported by Jamison for the hydrocarboxylation of styrenes, [4] has shown that the photochemical hydrocarboxylation of α,β‐unsaturated esters can also be carried out under flow conditions and some of the products containing all‐carbon quaternary centers can be accessed in good to excellent yield. Additionally, they showed that these products are versatile building blocks for lactonization.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 ] Recently Lan and Yu introduced a photochemical approach to a range of α,β‐unsaturated esters providing good yields of the corresponding β‐hydrocarboxylated products, using stoichiometric or catalytic aromatic thiols. [3a] Romo, utilizing the conditions originally reported by Jamison for the hydrocarboxylation of styrenes, [4] has shown that the photochemical hydrocarboxylation of α,β‐unsaturated esters can also be carried out under flow conditions and some of the products containing all‐carbon quaternary centers can be accessed in good to excellent yield. Additionally, they showed that these products are versatile building blocks for lactonization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a general and practical method is desirable. Inspired by recent visible-light-driven reductive carboxylations of different electrophiles with CO 2 44 59 , we wondered whether we could develop a general and practical strategy to achieve efficient and selective carboxylation of carbonyls with CO 2 via visible-light photoredox catalysis. Achieving such a goal requires addressing several challenges.…”
Section: Introductionmentioning
confidence: 99%
“… 5 ) and carboxylic acids. 6 Organic carbamates constitute an important class of compounds, which are widely used in agrochemicals, 7 pharmaceuticals 8 and as intermediates in organic synthesis. 9 Traditional methods for the preparation of carbamates are mainly based on the use of toxic phosgene and its derivatives, which are environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%